Modulation of Immune Tolerance via Siglec-Sialic Acid Interactions - Lübbers, Joyce; Rodríguez, Ernesto; van Kooyk, Yvette (Frontiers in Immunology, 2018)
One of the key features of the immune system is its extraordinary capacity to discriminate between self and non-self and to respond accordingly. Several molecular interactions allow the induction of acquired immune responses when a foreign antigen is recognized, while others regulate the resolution of inflammation, or the induction of tolerance to self-antigens. Post-translational signatures, such as glycans that are part of proteins (glycoproteins) and lipids (glycolipids) of host cells or pathogens, are increasingly appreciated as key molecules in regulating immunity versus tolerance. Glycans are sensed by glycan binding receptors expressed on immune cells, such as C-type lectin receptors (CLRs) and Sialic acid binding immunoglobulin type lectins (Siglecs), that respond to specific glycan signatures by triggering tolerogenic or immunogenic signalling pathways. Glycan signatures present on healthy tissue, inflamed and malignant tissue or pathogens provide signals for ‘’self’’ or “non-self” recognition. In this review we will focus on sialic acids that serve as “self” molecular pattern ligands for Siglecs. We will emphasize on the function of Siglec-expressing mononuclear phagocytes as sensors for sialic acids in tissue homeostasis and describe how the sialic acid-Siglec axis is exploited by tumors and pathogens for the induction of immune tolerance. Furthermore, we highlight how the sialic acid-Siglec axis can be utilised for clinical applications to induce or inhibit immune tolerance.